Fun Merdeka walk while flying the Jalur Gemilang - UMP, PNC (2019)
More than 100 Universiti Malaysia Pahang (UMP) staff took part in the Fun Walk: 1,000 Merdeka Steps that was held at UMP Pekan Campus on August 15, 2019.